Perilaku Merokok dan Risiko Penyakit Paru Kronis pada Lansia - Pratama, Andika; Arif, Arif; Ramadhan, Rizky (Lembaga Publikasi Ilmiah Nusantara, 2025)
Smoking is one of the main risk factors in the development of chronic lung disease, particularly among the elderly, who naturally experience a decline in lung function and immune resistance. This study aims to analyze the relationship between smoking behavior and the risk of chronic lung disease in the elderly. The research design used is quantitative with a cross-sectional approach. The sample consisted of 150 elderly individuals aged ≥60 years, selected through purposive sampling in the working area of Community Health Center X. Data were collected through interviews using structured questionnaires and lung health examinations using spirometry. The results showed that 68% of elderly individuals who were still actively smoking experienced symptoms of chronic lung disease, such as persistent cough, shortness of breath, and decreased lung capacity. Furthermore, it was found that a smoking duration of more than 20 years had a significant relationship with the severity of symptoms (p < 0.05). This study concludes that smoking behavior has a strong influence on the increased risk of chronic lung disease in the elderly. Therefore, it is important to implement promotive and preventive efforts, including health education, smoking cessation counseling, and routine lung health check-ups for the elderly population, in order to reduce the incidence and complications of chronic lung disease.